Effects of Lactobacillus salivarius supplementation on the growth performance, liver function, meat quality, immune responses and Salmonella Pullorum infection resistance of broilers challenged with Aflatoxin B1 - Chen, Xueping; Ishfaq, Muhammad; Wang, Jian (Poultry science, 2022)
Aflatoxin B1 (AFB1) is one of the most toxic mycotoxins. It has been reported that dietary exposure to AFB1 is related to the low growth performance, immunosuppression, and high susceptibility to infectious diseases of chickens. The aim of the present study was to evaluate the protective effects of Lactobacillus salivarius on broiler chickens challenged with AFB1. First, AFB1 degradation ability of Lactobacillus salivarius was measured by a high-performance liquid chromatography (HPLC) method. Then, the Arbor Acres broiler chickens were randomly assigned to experimental groups. The effects of Lactobacillus salivarius supplementation on the growth performance, liver function, and meat quality were measured, and immune response was also determined after vaccination with attenuated infectious bursal disease virus (IBDV) vaccine of broilers challenged with AFB1. Besides, resistance to Salmonella Pullorum infection along with AFB1 exposure was determined in broilers. The results showed that Lactobacillus salivarius could effectively degrade AFB1. Lactobacillus salivarius supplementation improved growth performance, liver function, and meat quality of broilers challenged with AFB1. In addition, Lactobacillus salivarius supplementation resulted in enhanced specific antibody and IFN-γ production, and lymphocyte proliferation in broilers challenged with AFB1 after IBDV vaccine immunization. Furthermore, Lactobacillus salivarius supplementation enhanced Salmonella Pullorum infection resistance in broilers challenged with AFB1. Our results revealed a tremendous potential of Lactobacillus salivarius as feed additive to degrading AFB1 and increasing broilers production performance in poultry production.